The Impact of Productive Zakat Utilization on the Improvement of Micro Enterprises and Religiosity of Mustahiqqs in Rusunawa Marunda, North Jakarta: A Study at Baznas DKI Jakarta Province - Desy Tri Rahmawati; Arief Mufraini (Green Publisher Indonesia, 2026)
The purpose of the study is to identify the relationship between the utilization of productive zakat to micro businesses and the relationship between the utilization of productive zakat and religiosity. This quantitative research is supported by literature such as books and internet sites, using a survey method through the distribution of questionnaires with a likert scale. To analyze the data, this study used Partial Least Square (PLS) with three measurement models: outer model, inner model, Goodness of Fit (GoF) criteria, and hypothesis testing. Primary data came from mustaḥiqq questionnaires and interviews conducted at the National Amil Zakat Agency of DKI Jakarta Province. Secondary data were obtained through literature studies and available information about the agency. The results of the study show that the utilization of productive zakat has a significant influence on the increase in micro businesses by 0.593. So that mustaḥiqq can meet the needs of life. Then the relationship between the utilization of productive zakat and the increase in religiosity, namely the utilization of productive zakat, has a positive and significant influence on the increase in religiosity by 0.550. So that mustaḥiqq becomes religious. This thesis has an argument that zakat religious institutions have a role in alleviating poverty by providing business capital and spiritual guidance through religious activities.